2016
DOI: 10.1128/aac.00602-16
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Physiological Conditions Promote Ciprofloxacin Resistance in Low-Level-Quinolone-Resistant Escherichia coli

Abstract: Escherichia coli isolates carrying chromosomally encoded low-level-quinolone-resistant (LLQR) determinants are frequently found in urinary tract infections (UTIs). LLQR mutations are considered the first step in the evolutionary pathway producing high-level fluoroquinolone resistance. Therefore, their evolution and dissemination might influence the outcome of fluoroquinolone treatments of UTI. Previous studies support the notion that low urine pH decreases susceptibility to ciprofloxacin (CIP) in E. coli. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
1
18
1
1
Order By: Relevance
“…These results demonstrate that urinary tract physiological conditions considerably affect the susceptibility of the isogenic and clinical Qnr strains, making all of them resistant to CIP in urine at pH 5. It should be noted here that the urine of more than 60% of the UTI patients had a pH of Յ6 (12). With the aim of testing how survival of Qnr strains under CIP treatment could be affected by urinary tract physiological conditions, we also determined the survival rates of isogenic strains in the presence of the maximum concentration of CIP attained in the bladder (ϳ1,000 g/ml) during the first 6 h of treatment, according to previous pharmacokinetic and pharmacodynamic (PK/PD) studies (26).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…These results demonstrate that urinary tract physiological conditions considerably affect the susceptibility of the isogenic and clinical Qnr strains, making all of them resistant to CIP in urine at pH 5. It should be noted here that the urine of more than 60% of the UTI patients had a pH of Յ6 (12). With the aim of testing how survival of Qnr strains under CIP treatment could be affected by urinary tract physiological conditions, we also determined the survival rates of isogenic strains in the presence of the maximum concentration of CIP attained in the bladder (ϳ1,000 g/ml) during the first 6 h of treatment, according to previous pharmacokinetic and pharmacodynamic (PK/PD) studies (26).…”
mentioning
confidence: 80%
“…Therefore, low-level quinolone-resistant Escherichia coli mutants have been traditionally considered to be susceptible according to standard susceptibility testing. However, we recently found that growth under physiological urinary tract conditions (i.e., growth in urine, at low pH values, and under anaerobiosis) conferred clinical levels of resistance to the fluoroquinolone ciprofloxacin (CIP) (12). This situation may provide a selective scenario for the evolution of high-level quinolone resistance and could lead to therapeutic failure in patients with urinary tract infection (UTI).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing ability of cipro oxacin-resistance or tolerance may lead to high clinical failure rate of bacterial infections and increasing prevalence of infections by antibiotic-resistant bacteria [4,5]. The canonical mechanisms of cipro oxacin-resistance include genetic mutations of gyrA and parC or horizontal dissemination of antibiotic resistance genes which protects or modi es the targets the uoroquinolone [6].…”
Section: Discussionmentioning
confidence: 99%
“…En el caso de la Escherichia coli, en la que se ha encontrado una mutación cromosómica denominada "low-level quinolone resistant (LLQR), es considerada el primer paso en la evolución a la alta resistencia a este tipo de fármaco. 7 Ahora bien, debe entenderse que el antibiótico no induce la resistencia, solamente la selecciona a través del proceso de selección natural, por lo que sobrevivirán aquellas variantes capaces de resistir las concentraciones del fármaco. 8 Debido a las ventajas que ofrecen las quinolonas, son las más elegidas para su uso clínico y; no obstante, debe evitarse el abuso o uso incorrecto de este medicamento ya que el uso irracional de antibióticos puede desembocar en la aparición de cepas resistentes con el riesgo sanitario de agotar las opciones para tratar las infecciones.…”
Section: )unclassified